2023
DOI: 10.2147/dddt.s419146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Remimazolam and Propofol on Emergence Agitation in Elderly Patients Undergoing Hip Replacement: A Clinical, Randomized, Controlled Study

Jinjuan Duan,
Xia Ju,
Xing Wang
et al.

Abstract: Purpose The aim of this study was to compare the effects of remimazolam and propofol on emergence agitation (EA) in elderly patients undergoing hip replacement. Methods A total of 60 elderly patients undergoing hip replacement were recruited for this prospective, single-center, clinical, randomized, controlled study from February to April 2023. They were randomly assigned to two groups: the remimazolam group (group R) and the propofol group (group P). In group R, remima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Recent studies suggested that the pharmacokinetics of remimazolam was not influenced by the baseline factors such as age, sex, and weight [ 36 ], without accumulation or prolonged efficacy even after a long-term or high-dose infusion [ 37 ]. Duan et al enrolled 60 elderly patients who had hip replacement to show that remimazolam anesthesia, when compared with propofol anesthesia, could reduce the incidence of emergence agitation [ 38 ]. Another recent study found that remimazolam anesthesia did not increase POD among elderly patients undergoing orthopedic surgical procedures [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that the pharmacokinetics of remimazolam was not influenced by the baseline factors such as age, sex, and weight [ 36 ], without accumulation or prolonged efficacy even after a long-term or high-dose infusion [ 37 ]. Duan et al enrolled 60 elderly patients who had hip replacement to show that remimazolam anesthesia, when compared with propofol anesthesia, could reduce the incidence of emergence agitation [ 38 ]. Another recent study found that remimazolam anesthesia did not increase POD among elderly patients undergoing orthopedic surgical procedures [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association of benzodiazepines with the occurrence of emergence delirium remains to be discussed. Nevertheless, recent studies have reported that remimazolam is associated with a decreased incidence of emergence delirium ( Duan et al, 2023 ; Yang et al, 2023 ). A study conducted by Duan et al found that remimazolam not only effectively reduced the incidence of ED compared with propofol but also demonstrated minor hemodynamic effects and a lower occurrence of postoperative adverse events in geriatric hip-replacement patients ( Duan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent studies have reported that remimazolam is associated with a decreased incidence of emergence delirium ( Duan et al, 2023 ; Yang et al, 2023 ). A study conducted by Duan et al found that remimazolam not only effectively reduced the incidence of ED compared with propofol but also demonstrated minor hemodynamic effects and a lower occurrence of postoperative adverse events in geriatric hip-replacement patients ( Duan et al, 2023 ). Yang et al demonstrated that older adult patients undergoing general anesthesia with remimazolam had a low incidence of emergence delirium, similar to propofol ( Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association of benzodiazepines with the occurrence of emergence delirium remains to be discussed. Nevertheless, recent studies have reported that remimazolam is associated with a decreased incidence of emergence delirium (Duan et al, 2023;Yang et al, 2023). A study conducted by Duan et al found that remimazolam not only effectively reduced the incidence of ED compared with propofol but also demonstrated minor hemodynamic effects and a lower occurrence of postoperative adverse events in geriatric hip-replacement patients (Duan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent studies have reported that remimazolam is associated with a decreased incidence of emergence delirium (Duan et al, 2023;Yang et al, 2023). A study conducted by Duan et al found that remimazolam not only effectively reduced the incidence of ED compared with propofol but also demonstrated minor hemodynamic effects and a lower occurrence of postoperative adverse events in geriatric hip-replacement patients (Duan et al, 2023). Yang et al demonstrated that older adult patients undergoing general anesthesia with remimazolam had a low incidence of emergence delirium, similar to propofol (Yang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%